Marriages Among the Representatives of the Houses of Kakheti Kingdom and Samegrelo Principality (XVI-XVIII Centuries) - Javakhishvili, Davit (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
The study examines the marriages among the representatives of the Houses of Kakheti and Kartli-Kakheti Kingdom and Principality of Samegrelo (Odishi, Mingrelia). These marriages strengthened the connection between the rulers of those kingdoms - Kakheti branch of Bagrationi royal dynasty and the ruling dynasty of Principality of Samegrelo – Dadiani. In the paper, the chronological examines such insolation that occurred four times: 1) In 1590, the daughter of King Alexander II of Kakheti (reigned in 1574-1601 and 1602-1605) - Princess Nestan-Darejan married the Sovereign Prince Manuchar I (ruled in 1590-1611). In 1591 Nestan-Darejan died at child-birth. Their son -Sovereign Prince Levan II (1591-1657) ruled in 1611-1657; 2) In 1750, King Erekle II (reigned in 1744-1762 - in Kakheti, in 1762-1798 - in Kartli-Kakheti) married the Princess Darejan Dadiani (1734-1807), daughter of Katsia/Giorgi Dadiani, whose nephew Sovereign Prince Katsia II ruled in 1757-1788; 3) In 1765, King Erekle II’s sister, the King’s Daughter Princess Elisabed (1750-1770) married the Sovereign prince Katsia II. Elisabed died at child-birth. Their son – Sovereign prince Grigol (1770-1804) ruled in 1788-1804; 4) In 1790, the grandson of Erekle II - princess Nino (1772-1847) married the Sovereign Prince Grigol Dadiani. After the death of her husband (1804), Nino as a regent ruled Principality of Odishi until adulthood of her son -Sovereign Prince Levan V (1793-1846), who ruled in 1810-1840.